Identification of Paenibacillus amylolyticus as the true causative agent for a nasal septum abscess: a case report - Rizalinda Sjahril; Valentine Hursepuny; Prajayanti Palulun; Nadyah; Andi Rofian Sultan (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2021)
Introduction: A bacteria commonly found in the environment was identified in a nasal septum abscess in a diabetic patient. The isolation of a common environment bacteria Paenibacillus amylolyticus from nasal septum abscess, particularly in a diabetic type 2 patient, was initiated argumentation whether to consider it a true pathogen that needs to be treated with antibiotics or as a contaminant that does not require antibiotic treatment. Thus, in this case, report, an evaluation of the pre-analytical and analytical phase of the laboratory identification aided in determining whether the bacterium is a contaminant or causative agent. Case description: A 58-year-old woman came to the Emergency Department with foul yellowish secretion from her left nostril that started three weeks before. She confessed to being diabetic but not under common control. Physical examination of the left nasal cavity showed signs of crust and fistula on the medial mucosal membrane, and an ulcer was seen at the upper sulcus ginggivo-buccal. Her blood pressure was 230/120 mmHg, her blood glucose was 270 mg/ dL, and her HbA1c was 13.5. Clinically, the diagnosis was nasal septum abscess with diabetes type 2 and hypertension grade 2. A swab sample was collected from the nasal lesion and transported to the laboratory at room temperature less than 2 hours. Direct Gram staining showed Gram-positive, rod-shaped bacteria1+, polymorphonuclear cells 3+ and epithelial 1+. Ziehl Neelsen staining was negative. While no growth was seen on chocolate agar, MacConkey agar and Saboraud dextrose agar, small greyish colonies grew on blood agar, which by Vitek2 System were identified as Paenibacillus amylolyticus. Conventional antibiotic sensitivity tests showed sensitivity to erythromycin and vancomycin. Accordingly, the patient was treated with erythromycin and metronidazole for ten days, and the nasal septum abscess was healed. Conclusion: The presence of spore-forming rod-shaped bacteria on blood agar identified as Paenibacillus amylolyticus. It was confirmed as the true causative agent of the nasal septum abscess based on the acceptable pre-analytical and analytical phases.